Antifungal Activity of Biocontrol Agents In Vitro and Potential Application to Reduce Mycotoxins (Aflatoxin B1 and Ochratoxin A) - Francisco Illueca; Pilar Vila-Donat; Jorge Calpe; Carlos Luz; Giuseppe Meca; Juan M. Quiles (Toxins, 2021)
Food bio-preservatives are requested as substituents of chemical pesticides in food. The aim of this study was to carry out a screening of twenty biocontrol agents (BCAs) for their potential fungicidal activity in vitro. Twenty BCAs were tested against ten pathogenic fungi. Some of the cell-free supernatants (CFS) tested showed in vitro antifungal activity versus pathogenic fungi. The highest fungicidal activity was observed in the fermented CFS of Paenibacillus chibensis CECT 375, Bacillus amyloliquefaciens CECT 493, and Pantoea agglomerans CECT 850, which showed a minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) values of 125 and 250 g/L, respectively. The compounds responsible for the antifungal activity, such as organic and phenolic acids, were determined. Lactic acid, acetic acid, benzoic acid, and phenyllactic acid among others can be related to antifungal activity. HPLC-MS/MS analysis showed a reduction of ochratoxin A (OTA) and aflatoxin B1 (AFB1) up to 26% (Paenibacillus alvei CECT 2) and 55% (Paenibacillus polymyxa CECT 155), respectively. The present study prompts that metabolism products of BCAs are propitious for the bioconservation of food, due to their ability to reduce the proliferation of mycotoxigenic fungi and mycotoxins production.